2013
DOI: 10.1111/evo.12183
|View full text |Cite
|
Sign up to set email alerts
|

EXPLORING THE SOCIOBIOLOGY OF PYOVERDIN-PRODUCINGPSEUDOMONAS

Abstract: The idea that bacteria are social is a popular concept with implications for understanding the ecology and evolution of microbes. The view arises predominately from reasoning regarding extracellular products, which, it has been argued, can be considered "public goods." Among the best studied is pyoverdin-a diffusible iron-chelating agent produced by bacteria of the genus Pseudomonas.Here we report the de novo evolution of pyoverdin nonproducing mutants, genetically characterize these types and then test the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
119
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 86 publications
(207 reference statements)
4
119
0
Order By: Relevance
“…In contrast to this pattern, we observed further degradation of pyoverdine production in the pvdS_prom background almost exclusively in iron-rich environments regardless of spatial structure. Because pyoverdine is not needed under iron-rich conditions, yet still expressed in low amounts [14,25], we assume that selection against pyoverdine production represents the erosion of an unnecessary trait.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this pattern, we observed further degradation of pyoverdine production in the pvdS_prom background almost exclusively in iron-rich environments regardless of spatial structure. Because pyoverdine is not needed under iron-rich conditions, yet still expressed in low amounts [14,25], we assume that selection against pyoverdine production represents the erosion of an unnecessary trait.…”
Section: Discussionmentioning
confidence: 99%
“…In many ecological situations, bacteria form complex, tightly packed, and spatially structured colonies, such as biofilms, where public good dispersal may be severely reduced compared with planktonic cultures. This raises the questions of how public good molecules circulate between cells in these natural conditions and how cooperation is affected by the population structure (8,(13)(14)(15). Experimental realizations of limited public good dispersal were obtained by tuning the viscosity (16), the distance between colonies of producers and nonproducers (17), or the amount of cell attachment (18).…”
mentioning
confidence: 99%
“…In liquid conditions, mutants that do not produce siderophores have, in fact, been shown to outcompete WT strains (5)(6)(7)(8). However, the limited spatial dispersal of public goods can challenge this picture and has been proposed as a general mechanism for explaining the maintenance of cooperation (8)(9)(10)(11)(12). When dispersal is limited, public good molecules tend to stay in the vicinity of the producing subpopulations, allowing them to benefit preferentially from their own production, and thus to balance the advantage of opportunistic nonproducing strains.…”
mentioning
confidence: 99%
“…However, the study of microbes also poses significant challenges, foremost among which is a lack of knowledge of the ecological context under which the supposedly cooperative trait has evolved and is maintained (O'Brien and Brockhurst, 2015;Rainey, 2015;Zhang and Rainey, 2013). Here, ecology encapsulates both the biotic (interactions among organisms) and the abiotic (interactions between organisms and their environment) dimensions (see Glossary).…”
Section: Introductionmentioning
confidence: 99%
“…Here, ecology encapsulates both the biotic (interactions among organisms) and the abiotic (interactions between organisms and their environment) dimensions (see Glossary). When seemingly cooperative and cheating traits have been studied in different ecological contexts, a variety of genotypeby-environment interactions have been found that have questioned the appropriateness of sociobiological labels (Driscoll et al, 2011;Dubravcic et al, 2014;Redfield, 2002;Tarnita et al, 2015;Zhang and Rainey, 2013). Moreover, the rapid evolutionary pace also entails that traits can be selected for on a fast timescale that affects the ecology of the microbes, from intraspecific and interspecific interactions to the level of the ecosystem (Lennon and Denef, 2015), leading to crucial ecoevolutionary feedback.…”
Section: Introductionmentioning
confidence: 99%